The Blackwell Encyclopedia of Sociology 2015
DOI: 10.1002/9781405165518.wbeoss198.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Socialization and Sport

Abstract: There is a long tradition of research on socialization and sport. Roots of this research are grounded in theories on play in child development, in progressive‐era notions that team sports constituted an environment in which valuable lessons could be learned, and in popular twentieth‐century assumptions that playing sports was an inherently character‐building experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Some tweets emphasized how the pandemic had disrupted their main ways of socializing with other people and establishing ties with their family and peers, as Parnell et al [ 62 ] identified. Others referred to the desire to recover positive social and personal outcomes assigned to sports as experienced before the outbreak that, according to Coakley [ 63 ], reminded one of the socialization effects taken for granted in Western societies since the emergence of modern sport. These messages continue to show how people value sport as a self-evident good and the inspirational role they assign to it for the entire society, affirming what Delaney [ 64 ] identified as a functionalist view of sport that supports the social order.…”
Section: Discussionmentioning
confidence: 99%
“…Some tweets emphasized how the pandemic had disrupted their main ways of socializing with other people and establishing ties with their family and peers, as Parnell et al [ 62 ] identified. Others referred to the desire to recover positive social and personal outcomes assigned to sports as experienced before the outbreak that, according to Coakley [ 63 ], reminded one of the socialization effects taken for granted in Western societies since the emergence of modern sport. These messages continue to show how people value sport as a self-evident good and the inspirational role they assign to it for the entire society, affirming what Delaney [ 64 ] identified as a functionalist view of sport that supports the social order.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, sports club activities could be seen as a protective factor in young boys. Nevertheless, as the results are based on a cross‐sectional study, it is not possible to assume simply socialisation effects through sports club activities (among others, Coakley, 2007). It may also be possible that boys who engaged in sports club activities were already satisfied with their body and merely looked for a context in which to confirm their body ideals.…”
Section: Discussionmentioning
confidence: 99%
“…Its rituals, rules, norms, flow, and even its athletes all follow structured and patterned ways of playing the game that work to create social stability. Because of this, sports have always been a successful means of socializing children by teaching them to follow rules and order (Coakley 1996; Hasbrook 1999). On the other hand, performatives tend to defy convention and favor confrontation.…”
Section: Sport Performance and Performativitymentioning
confidence: 99%